Mud - Nichols, Jeff, 1978-; Falcone, Lisa Maria; Green, Sarah, 1957-; Ryder, Aaron; McConaughey, Matthew, 1969-; Sheridan, Tye, 1996-; Lofland, Jason; Shepard, Sam, 1943-; Witherspoon, Reese, 1976-; Paulson, Sarah, 1974-; Shannon, Michael, 1974-; Baker, Joe Don.; et al. (Santa Monica, CA : Lionsgate, 2013)
Two boys, Ellis and his best friend Neckbone, find a mysterious man named Mud hiding out on a deserted island in the Mississippi. Mud tells the boys fantastic stories about his life, including how he killed a man in Texas and vengeful bounty hunters are coming to get him. He says he is planning to meet and escape with the love of his life, Juniper. The boys agree to help him, but it isn't long until their small town is besieged by bounty hunters out for blood.
DVD; region1; widescreen presentation; 5.1 Dolby digital.
English or Spanish dialogue; English or Spanish subtitles; closed captioned.
Title from container.
Matthew McConaughey, Tye Sheridan, Jacob Lofland, Sam Shepard, Reese Witherspoon, Sarah Paulson, Michael Shannon, Joe Don Baker, Ray McKinnon.
Originally released as a motion picture in 2012.
Rating: PG-13; for sexuality, a scene of war violence, some language, thematic elements and smoking.
Keywords: Friendship -- Drama; Fugitives from justice -- Drama; Murder -- Drama; Islands -- Drama; Mississippi River -- Drama; Amistad -- Teatro; Asesinato -- Teatro; Feature films; Coming-of-age films; Crime films; Action and adventure films; Fiction films; Video recordings for the hearing impaired